Improving Resident Self-Efficacy in Tracheostomy Management Using a Novel Curriculum - J. Benjamin; K. Roy; G. Paul; S. Kumar; E. Charles; E. Miller; H. Narsi-Prasla; J. D. Mahan; S. Thammasitboon (Association of American Medical Colleges, 2020)
Introduction Patients receiving pediatric tracheostomy have significant risk for mortality due to compromised airway. Timely management of airway emergencies in children with tracheostomies is an important clinical skill for pediatricians. We developed this curriculum to improve residents' self-efficacy with tracheostomy management. Methods We collected baseline data on 67 residents from two hospitals while creating a blended curriculum with video-based instruction on routine tracheostomy change and team management of tracheostomy emergency. Forty residents enrolled in the curriculum. During an ICU rotation, they received face-to-face instruction on routine tracheostomy change in small groups, followed by assessment of managing a tracheostomy emergency during a simulation. A video completed prior to the simulation took 9 minutes, the routine tracheostomy change didactic session took 15 minutes, and the simulation instruction was completed in 10-15 minutes. We collected feedback on the effectiveness of the curriculum from the participants. Results All 107 residents from the baseline and intervention groups completed the self-efficacy survey. The intervention group had significantly higher changes in scores across all self-efficacy domains than the baseline group. On the curriculum feedback survey, residents rated the curriculum very highly, between 4.4 and 4.8 on a 5-point Likert scale. Discussion Our blended curriculum increased learners' self-efficacy and promoted learner competence in tracheostomy management. Residents scored more than 80% across all aspects of simulation assessment and reported higher self-efficacy scores following our curricular intervention.